Combined resection of the transpancreatic common hepatic artery preserving the gastric arterial arcade without arterial reconstruction in hepatopancreatoduodenectomy: a case report - Takashi Miyata; Yusuke Yamamoto; Teiichi Sugiura; Yukiyasu Okamura; Takaaki Ito; Ryo Ashida; Sunao Uemura; Yoshiyasu Kato; Katsuhisa Ohgi; Atsushi Kohga; Tsuneyuki Uchida; Shusei Sano; et al. (Surgical Case Reports, 2018)
Abstract Background Surgeons sometimes must plan pancreatoduodenectomy (PD) for patients with a variant common hepatic artery (CHA) branching from the superior mesenteric artery (SMA) penetrating the pancreatic parenchyma, known as a transpancreatic CHA (tp-CHA). Case presentation A 67-year-old man was admitted to our hospital because of liver dysfunction. A duodenal tumor was identified by gastrointestinal endoscopy, and a biopsy revealed a neuroendocrine tumor. Computed tomography showed multiple metastases in the left three sections of the liver. As an anatomical variant, the CHA branched from the SMA and passed through the parenchyma of the pancreatic head, and all hepatic arteries branched from the CHA. Furthermore, the arcade between the left and right gastric artery (RGA) was detected, and the RGA branched from the root of the left hepatic artery. PD and left trisectionectomy of the liver were performed. The tp-CHA was resected with the pancreatic head, and the gastric arterial arcade was preserved to maintain the right posterior hepatic arterial flow. Postoperatively, there were no signs of hepatic ischemia. Conclusions When planning PD, including hepatopancreatoduodenectomy, for patients with a tp-CHA, surgeons should simulate various situations for maintaining the hepatic arterial flow. The preservation of the gastric arterial arcade is an option for maintaining the hepatic arterial flow to avoid arterial reconstruction.